Castleman Disease: An Unexpected Cause of a Solitary Pleural Mass. (11th September 2013) - Moloney, Fiachra; Twomey, Maria; Hinchion, John; Maher, Michael
Abstract : Castleman disease (CD) is a rare benign lymphoproliferative disorder, the etiology of which is unclear. Clinically it may manifest as localized disease (unicentric) or disseminated disease (multicentric). CD occurs in the thorax in 70% of cases, abdomen and pelvis in 15%, and in the neck in 10–15% of cases. We present a case of a pleural mass located posteriorly in a paraspinal location, which was discovered incidentally in a 50-year-old man and was subsequently resected followed by an unexpected diagnosis of Castleman disease on histological examination. In this report, we review the clinical and histological findings in a rare presentation of Castleman disease and discuss the findings in this case as part of an overall review of the typical radiological findings seen in Castleman disease.